The incidence and influencing factors of hypertensive disorders during pregnancy in hangzhou, China, between 2012 and 2021 - Yiming Chen; Bin Wu; Huimin Zhang; Xuelian Chu; Lingling Huang; Yanan Wang; Xiufeng Liang (Heliyon)
Objective: To analyze the incidence and influencing factors of hypertensive disorders of pregnancy (HDP) in Hangzhou, China, between 2012 and 2021. Methods: We conducted a retrospective cohort study to analyze data relating to 155,433 pregnant women in Hangzhou, China, who were divided into eight groups: gestational hypertension (GH, 4247 cases), preeclampsia (PE, 1602 cases), severe preeclampsia (SPE, 995 cases), eclampsia (9 cases), HELLP syndrome (43 cases), chronic hypertension (43 cases), chronic hypertension combined with PE or SPE (77 cases), postpartum eclampsia (5 cases), and pregnant women with normal blood pressure (148412 cases). Odds ratios (ORs) and 95 % confidence intervals (95 % CIs) were used to show the association of factors with HDP. Results: The total incidence of HDP was 45.17 ‰ (95 % CI: 44.14‰–46.20 ‰), and the subtypes of HDP showed an increasing trend from 2012 to 2021 (all P < 0.01). Several maternal characteristics, including maternal age (ORGH = 1.158 (1.035–1.295), 1.697 (1.478–1.948), and 2.769 (2.234–3.433), ORPE = 1.526 (1.224–1.902) to 2.506 (1.796–3.497)), non-local residence (OR = 1.124 (1.018–1.241), 1.212 (1.032–1.423), and 1.222 (1.010–1.479)), in vitro fertilization (OR = 1.263 (1.028–1.551), 1.342 (1.042–1.729) and 1.692 (1.234–2.321)), graviditas ≤1 (ORGH = 1.126 (1.035–1.226)), parity <1 (ORGH = 1.140 (1.026–1.265), ORPE = 1.336 (1.130–1.581)), non-vaginal delivery (ORGH = 1.525 (1.223–1.901), 1.185 (1.058–1.328) an 1.753 (1.612–1.908); ORpe = 2.108 (1.428–3.112), 1.464 (1.174–1.826) and 4.205 (3.643–4.854), and ORspe = 7.000 (3.517–13.930), 1.914 (1.217–3.010) and 19.981 (14.936–26.730)), maternal hospitalization >7 days (OR = 2.098 (1.921–2.291), 2.115 (1.857–2.409), and 1.553 (1.333–1.810)), and winter birth (ORGH = 1.297 (1.196–1.408), ORPE = 1.425 (1.242–1.636)), were all identified as risk factors for GH, PE, and SPE. Furthermore, HDP may increase the risk of gestational period <37 weeks, low birth weight (LBW), fetal macrosomia, and a birth length <50 cm (all P < 0.05). Conclusions: The incidence of HDP and its subtypes showed an overall increasing trend from 2012 to 2021. Maternal factors and pregnancy outcomes may be strongly associated with HDP.